2014
DOI: 10.1586/17474124.2014.876357
|View full text |Cite
|
Sign up to set email alerts
|

Hepatitis C virus infection in patients with HIV-1: epidemiology, natural history and management

Abstract: Hepatitis C virus (HCV)-related liver diseases have contributed to increased morbidity and mortality in HIV-1-infected individuals in the era of effective antiretroviral therapy. HCV transmission patterns have changed among the HIV co-infected population during the last decade, with acute HCV infection emerging worldwide. HIV infection accelerates the progression of HCV-related liver diseases and consequently cirrhosis, liver failure, and hepatocellular carcinoma. However, the current standard treatment of HCV… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 157 publications
1
13
0
Order By: Relevance
“…Given the shared modes of transmission, HCV/HIV coinfection is common, particularly among IDUs . HIV infection can cause a more rapid progression to liver diseases in HCV patients, contributing to higher mortality due to cirrhosis and HCC . HCV, especially genotype 3, coinfection with HIV would possibly increase treatment difficulty.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Given the shared modes of transmission, HCV/HIV coinfection is common, particularly among IDUs . HIV infection can cause a more rapid progression to liver diseases in HCV patients, contributing to higher mortality due to cirrhosis and HCC . HCV, especially genotype 3, coinfection with HIV would possibly increase treatment difficulty.…”
Section: Discussionmentioning
confidence: 99%
“…[47][48][49] HIV infection can cause a more rapid progression to liver diseases in HCV patients, contributing to higher mortality due to cirrhosis and HCC. 50 This study had several limitations worth noting. First, insufficient representativeness was inevitable with respect to genotyping methods, study period, and risk group, as all data were obtained from the published literature.…”
Section: Distribution Of Mixed Infection With Different Hcv Genotypesmentioning
confidence: 94%
“…The estimated HCV seroprevalence of the Chilean general population is 0.3% [37,38], while epidemiological data on HIV/HCV coinfection derive from a single center, which reported a prevalence of 2.6% [21,35]. Since the introduction of highly active ART resulted in an overall decrease of AIDS-related mortality, end stage liver disease caused by HCV has gained importance as a cause of mortality in PLWH [39]. Similar to HBV, patients with HIV/HCV coinfection progress more frequently and faster to liver fibrosis and cirrhosis and have a higher risk of HCC.…”
Section: Introductionmentioning
confidence: 99%
“…Similar to HBV, patients with HIV/HCV coinfection progress more frequently and faster to liver fibrosis and cirrhosis and have a higher risk of HCC. In addition, HCV treatment in PLWH is less effective [23,39]. The role of HCV as a co-factor in HIV disease progression remains controversial, but some studies have found lower absolute CD4+ cell counts and reduced immunological and virological responses after ART initiation [32,40,41].…”
Section: Introductionmentioning
confidence: 99%
“…Hepatitis C virus (HCV) infects an estimated 2.6%−3.1% of the world population and is a leading cause of liver disease [ 1 ].Without treatment, approximately 80% of patients with acute HCV infection progress to develop chronic infection and are at long-term risk for cirrhosis, hepatocellular carcinoma, and decompensated liver disease [ 2 ]. In HIV-infected individuals, HCV coinfection is common and the seroprevalence ranges from <5% in low-risk patients, 5−10% among MSM, to 50−90% among injection drug users (IDU) [ 3 ]. In HIV/HCV-coinfected individuals, HCV disease progresses more rapidly than HCV-monoinfected individuals and has become a leading cause of non-AIDS death [ 4 11 ].…”
Section: Introductionmentioning
confidence: 99%